The great pretenders? Individuals’ responses to threats to their remote worker identities - Felix, Bruno; Tiussi, Bruno Lorencini; Mahadevan, Jasmin; Dias, Rogério Correia (Frontiers in Psychology, 2023)
Introduction This study aims to understand (a) how remote workers respond to threats to their identity and (b) the conditions in which each coping response tends to occur more frequently. Methods To this end, we pursued a grounded theory approach, conducting interviews with 71 individuals who chose to work remotely. Results Our model and theoretical propositions create insights into how remote workers respond to negative stigma from a range of origins. While some responses lead to restructuring the remote workers’ identity (identity restructuring responses), others involve keeping the enactment of such identity (identity-preserving responses) or maintaining a paradoxical relationship between restructuring and preserving the identity (paradoxical identity work responses). We also theorise on the conditions under which each response is more likely to occur. Discussion We expand the predominant focus on the meso and macro aspects of this type of work to the micro-interactions in which these individuals engage, thus highlighting how identity is made, performed, created, and enacted, within specific boundary conditions. In addition, by reflecting upon remote workers’ identity threats in light of the wider macro context. We also explore the conditions under which specific kinds of responses tend to emerge.